The First Reconstruction of the Head Anatomy of a Cretaceous Insect, †Gerontoformica gracilis (Hymenoptera: Formicidae), and the Early Evolution of Ants. Issue 5 (27th September 2022) - Richter, Adrian; Boudinot, Brendon; Yamamoto, Shûhei; Katzke, Julian; Beutel, Rolf Georg
Abstract: The fossil record allows a unique glimpse into the evolutionary history of organisms living on Earth today. We discovered a specimen of the stem group ant † Gerontoformica gracilis (Barden and Grimaldi, 2014 ) in Kachin amber with near-complete preservation of internal head structures, which we document employing µ-computed-tomography-based 3D reconstructions. We compare † Gerontoformica to four outgroup taxa and four extant ant species, employing parsimony and Bayesian ancestral state reconstruction to identify morphological differences and similarities between stem and crown ants and thus improve our understanding of ant evolution through the lens of head anatomy. Of 149 morphological characters, 87 are new in this study, and almost all applicable to the fossil. † Gerontoformica gracilis shares shortened dorsal tentorial arms, basally angled pedicels, and the pharyngeal gland as apomorphies with other total clade Formicidae. Retained plesiomorphies include mandible shape and features of the prepharynx. Implications of the reconstructed transitions especially for the ant groundplan are critically discussed based on our restricted taxon sampling, emphasizing the crucial information derived from internal anatomy which is applied to deep time for the first time. Based on the falcate mandible in † Gerontoformica and other Aculeata, we present hypotheses for how the shovel-shaped mandibles in crown Formicidae could have evolved. Our results support the notion of † Gerontoformica as 'generalized' above-ground predator missing crucial novelties of crown ants which may have helped the latter survive the end-Cretaceous extinction. Our study is an important step for anatomical research on Cretaceous insects and a glimpse into the early evolution of ant heads. Graphical Abstract: